Assessing English Language Proficiency Among Hospitality Employees: A Qualitative Study at Aksmi Suites and Villas, Ubud, Bali 2026 - I Kadek Agus Bisena; Kadek Yogi Susana; Agus Ari Iswara (Journal of Comprehensive Science, 2026)
This study examines English language proficiency among employees at Aksmi Suites and Villas, Ubud, Bali, in response to the growing demand for effective communication in the hospitality industry. The increasing number of international tourists, many of whom use English as a primary language for communication, makes English competence a crucial factor in delivering high-quality hospitality services. The objective of this research is to assess employees’ English proficiency levels, identify communication challenges encountered during daily operations, and analyze their implications for improving service quality. A descriptive qualitative method was employed, involving 17 employees from various departments, including Front Office, Housekeeping, Food and Beverage, Kitchen, Engineering, Security, and Management. Data were collected through semi-structured interviews, direct English conversations, and workplace observations, and were analyzed using thematic analysis. The findings reveal that only a small proportion of employees demonstrate good English proficiency, while most exhibit moderate proficiency levels, and several still experience difficulties in using English effectively. The communication challenges identified include limited vocabulary, difficulties in understanding diverse accents, low confidence in speaking English, and an inability to handle guest complaints effectively. These limitations directly affect service consistency, communication effectiveness, and responsiveness. The study concludes that English proficiency significantly influences hospitality service quality, particularly within an international tourism environment. Therefore, structured and continuous English training programs are recommended to improve employee competence and enhance guest satisfaction and overall service performance at the resort.